Bicycle ownership, use, and injury patterns among elementary schoolchildren. Issue 4 (December 1995) - Waller, Julian A
Abstract : Patterns of bicycle ownership and injury were studied over a four month period among over 6000 schoolchildren. Two thirds of the bikes owned were standard style and one third high rise. Boys more often had high rise bikes. Slightly over 2% of bike owners are injured annually, but no differences were found according to bike style either in injury rate or severity. Bike borrowing and riding double were common factors in the injury events. Injury from spokes and loss of control because of loose handlebars were identified as problems resulting from product design.